1996
DOI: 10.1203/00006450-199606000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Undetectable Interleukin (IL)-10 and Persistent IL-8 Expression Early in Hyaline Membrane Disease: A Possible Developmental Basis for the Predisposition to Chronic Lung Inflammation in Preterm Newborns

Abstract: We are interested in determining whether premature birth alters expression of counterregulatory cytokines which modulate lung inflammation. Production of proinflammatory cytokines tumor necrosis factor alpha. IL-1 beta, and IL-8 is regulated in part by the antiinflammatory cytokine IL-10. For preterm newborns with hyaline membrane disease, deficiencies in the ability of lung macrophages to express antiinflammatory cytokines may predispose to chronic lung inflammation. We compared the expression of pro- and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
174
10
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(199 citation statements)
references
References 42 publications
13
174
10
2
Order By: Relevance
“…26,33 -35 Cellular IL-10 mRNA was undetectable in most airway samples of preterm infants with RDS, but it was expressed in all cell samples of term infants with meconium aspiration syndrome. 26 However, lung inflammatory cells of preterm infants exposed to IL-10 in vitro responded with a reduced expression of proinflammatory cytokines. 36 An imbalance between proinflammatory and anti-inflammatory cytokines can be considered as an important feature of lung injury.…”
Section: Inflammatory Cells Endothelial Interactions and Chemotaxismentioning
confidence: 99%
“…26,33 -35 Cellular IL-10 mRNA was undetectable in most airway samples of preterm infants with RDS, but it was expressed in all cell samples of term infants with meconium aspiration syndrome. 26 However, lung inflammatory cells of preterm infants exposed to IL-10 in vitro responded with a reduced expression of proinflammatory cytokines. 36 An imbalance between proinflammatory and anti-inflammatory cytokines can be considered as an important feature of lung injury.…”
Section: Inflammatory Cells Endothelial Interactions and Chemotaxismentioning
confidence: 99%
“…Jones et al 4 demonstrated increased production of inflammatory cytokines in preterm infants with MAS. Castelheim 10 showed compliment activation in human monocytes culture of MAS model.…”
Section: Human Studiesmentioning
confidence: 99%
“…17 Now we describe the pathways of induction of inflammatory response following cell influx. 4 Preterm and term newborns Production of TNFa, IL1b, and IL8 is regulated by IL-10; IL-10 not detected in preterm infants with or without MAS de Beaufort et al 8 Newborn infants Overexpression of IL-8 in MAS in vitro; increased migration of neotrophils; anti-IL-8 antibodies inhibit neutrophil migration Uotila and Kaapa 9 Human monocytes In culture increase of cycloxygenase-2 expression in vitro Castellheim et al 10 Human monocytes in culture Complement activation in MAS Animal models of MAS Tyler et al 3 Animal models Surfactant inactivation, chemical pneumonitis, airway obstruction, direct toxic damage of animal lung tissues Zagariya et al 6 Rabbit pups Intense inflammatory reactions involved in meconium-induced injury in vivo; expression of endothelin 1 in MAS Davey et al 11 Piglets Acute decrease in gas exchange and dynamic lung compliance; increase of total lung protein; inhibition of surfactant Holopainen et al 12 Piglets Inflammation, airway epithelium targeted, necrotic changes, phospholipase 2 activity increased. Mollnes et al 13 Animal models Complement activation in MAS Khan et al 14 Mice Increase of IL-13 expression in MAS in vivo; lymphocytic and eosinophilic inflammation Zagariya et al 15 Rabbit pups Phospholipase A2 activates apoptosis, influx of T-lymphocytes and macrophages in vivo; increase of TNFa, IL-1b, IL-6 and IL-8 in MAS in vivo Zagariya et al 16 Rabbit pups Cell death by apoptosis, influx of neutrophils and macrophages in vivo Tessler et al 17 Newborn infants Reactive oxygen species in vitro…”
Section: Inflammatory Responses To Meconiummentioning
confidence: 99%
See 2 more Smart Citations